Mega Planning : Practical Tools for Organizational Success. - Kaufman, Dr. Roger (SAGE Publications, 1999)
Mega Planning involves significant stakeholders in defining success and then identifies what each person and part of an organization must do to succeed. The author uses proven techniques, and covers the basic h̀ow-to's' of quality management, needs assessment, gap analysis, benchmarking, reengineering, and continuous improvement.